Download presentation

1
3 DERIVATIVES

2
**3.5 The Chain Rule In this section, we will learn about:**

DERIVATIVES 3.5 The Chain Rule In this section, we will learn about: Differentiating composite functions using the Chain Rule.

3
**Suppose you are asked to differentiate the function**

CHAIN RULE Suppose you are asked to differentiate the function The differentiation formulas you learned in the previous sections of this chapter do not enable you to calculate F’(x).

4
CHAIN RULE Observe that F is a composite function. In fact, if we let and let u = g(x) = x2 + 1, then we can write y = F(x) = f (g(x)). That is, F = f ◦ g. The derivative of the composite function f ◦ g is the product of the derivatives of f and g. This fact is one of the most important of the differentiation rules. It is called the Chain Rule.

5
**It seems plausible if we interpret derivatives as rates of change.**

CHAIN RULE It seems plausible if we interpret derivatives as rates of change. du/dx as the rate of change of u with respect to x dy/du as the rate of change of y with respect to u dy/dx as the rate of change of y with respect to x If u changes twice as fast as x and y changes three times as fast as u, it seems reasonable that y changes six times as fast as x. So, we expect that:

6
THE CHAIN RULE If g is differentiable at x and f is differentiable at g(x), the composite function F = f ◦ g defined by F(x) = f(g(x)) is differentiable at x and F’ is given by the product: F’(x) = f’(g(x)) • g’(x) In Leibniz notation, if y = f(u) and u = g(x) are both differentiable functions, then:

7
**Let ∆u be the change in corresponding to a change of ∆x in x, that is,**

COMMENTS ON THE PROOF Let ∆u be the change in corresponding to a change of ∆x in x, that is, ∆u = g(x + ∆x) - g(x) Then, the corresponding change in y is: ∆y = f(u + ∆u) - f(u)

8
**It is tempting to write:**

COMMENTS ON THE PROOF Equation 1 It is tempting to write:

9
COMMENTS ON THE PROOF The only flaw in this reasoning is that, in Equation 1, it might happen that ∆u = 0 (even when ∆x ≠ 0) and, of course, we can’t divide by 0.

10
**or, if y = f(u) and u = g(x), in Leibniz notation:**

CHAIN RULE Equations 2 and 3 The Chain Rule can be written either in the prime notation (f ◦ g)’(x) = f’(g(x)) • g’(x) or, if y = f(u) and u = g(x), in Leibniz notation:

11
CHAIN RULE Equation 3 is easy to remember because, if dy/du and du/dx were quotients, then we could cancel du. However, remember: du has not been defined du/dx should not be thought of as an actual quotient

12
**Find F’(x) if One way of solving this is by using Equation 2.**

CHAIN RULE E. g. 1—Solution 1 Find F’(x) if One way of solving this is by using Equation 2. At the beginning of this section, we expressed F as F(x) = (f ◦ g))(x) = f(g(x)) where and g(x) = x2 + 1.

13
Solution: E. g. 1—Solution 1 Since we have

14
**We can also solve by using Equation 3.**

Solution: E. g. 1—Solution 2 We can also solve by using Equation 3. If we let u = x2 + 1 and then:

15
**In using the Chain Rule, we work from the outside to the inside.**

NOTE In using the Chain Rule, we work from the outside to the inside. Equation 2 states that we differentiate the outer function f [at the inner function g(x)] and then we multiply by the derivative of the inner function.

16
CHAIN RULE Example 2 Differentiate: y = sin(x2) y = sin2 x

17
**So, the Chain Rule gives:**

Solution: Example 2 a If y = sin(x2), the outer function is the sine function and the inner function is the squaring function. So, the Chain Rule gives:

18
Solution: Example 2 b Note that sin2x = (sin x)2. Here, the outer function is the squaring function and the inner function is the sine function. Therefore,

19
**COMBINING THE CHAIN RULE**

In general, if y = sin u, where u is a differentiable function of x, then, by the Chain Rule, Thus,

20
**If n is any real number and u = g(x) is differentiable, then**

POWER RULE WITH CHAIN RULE Rule 4 If n is any real number and u = g(x) is differentiable, then Alternatively,

21
**POWER RULE WITH CHAIN RULE**

Example 3 Differentiate y = (x3 – 1)100 Taking u = g(x) = x3 – 1 and n = 100 in the rule, we have:

22
**Find f’ (x) if First, rewrite f as f(x) = (x2 + x + 1)-1/3 Thus,**

POWER RULE WITH CHAIN RULE Example 4 Find f’ (x) if First, rewrite f as f(x) = (x2 + x + 1)-1/3 Thus,

23
**POWER RULE WITH CHAIN RULE**

Example 5 Find the derivative of Combining the Power Rule, Chain Rule, and Quotient Rule, we get:

24
**Differentiate: y = (2x + 1)5 (x3 – x + 1)4**

CHAIN RULE Example 6 Differentiate: y = (2x + 1)5 (x3 – x + 1)4 In this example, we must use the Product Rule before using the Chain Rule.

25
Solution: Example 6 Thus,

26
Solution: Example 6 Noticing that each term has the common factor 2(2x + 1)4(x3 – x + 1)3, we could factor it out and write the answer as: Figure 3.5.1, p. 159

27
**Suppose that y = f(u), u = g(x), and x = h(t), **

CHAIN RULE Suppose that y = f(u), u = g(x), and x = h(t), where f, g, and h are differentiable functions, then, to compute the derivative of y with respect to t, we use the Chain Rule twice:

28
CHAIN RULE Example 7 If Notice that we used the Chain Rule twice.

29
CHAIN RULE Example 8 Differentiate The outer function is the square root function, the middle function is the secant function, and the inner function is the cubing function. Thus,

30
**According to the definition of a derivative, we have:**

HOW TO PROVE THE CHAIN RULE Recall that if y = f(x) and x changes from a to a + ∆x, we defined the increment of y as: ∆y = f(a + ∆x) – f(a) According to the definition of a derivative, we have:

31
**HOW TO PROVE THE CHAIN RULE**

So, if we denote by ε the difference between the difference quotient and the derivative, we obtain:

32
**HOW TO PROVE THE CHAIN RULE**

However, If we define ε to be 0 when ∆x = 0, then ε becomes a continuous function of ∆x .

33
**Thus, for a differentiable function f, we can write:**

HOW TO PROVE THE CHAIN RULE Equation 5 Thus, for a differentiable function f, we can write: ε is a continuous function of ∆x. This property of differentiable functions is what enables us to prove the Chain Rule.

34
**∆u = g’(a) ∆x + ε1 ∆x = [g’(a) + ε1] ∆x**

PROOF OF THE CHAIN RULE Equation 6 Suppose u = g(x) is differentiable at a and y = f(u) at b = g(a). If ∆x is an increment in x and ∆u and ∆y are the corresponding increments in u and y, then we can use Equation 5 to write ∆u = g’(a) ∆x + ε1 ∆x = [g’(a) + ε1] ∆x where ε1 → 0 as ∆x → 0

35
**∆y = f’(b) ∆u + ε2 ∆u = [f’(b) + ε2] ∆u**

PROOF OF THE CHAIN RULE Equation 7 Similarly, ∆y = f’(b) ∆u + ε2 ∆u = [f’(b) + ε2] ∆u where ε2 → 0 as ∆u → 0.

36
PROOF OF THE CHAIN RULE If we now substitute the expression for ∆u from Equation 6 into Equation 7, we get: So,

37
**As ∆x→ 0, Equation 6 shows that ∆u→ 0.**

PROOF OF THE CHAIN RULE As ∆x→ 0, Equation 6 shows that ∆u→ 0. So, both ε1 → 0 and ε2 → 0 as ∆x→ 0.

38
**This proves the Chain Rule.**

PROOF OF THE CHAIN RULE Therefore, This proves the Chain Rule.

Similar presentations

© 2021 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google